2022
DOI: 10.1007/s12626-022-00109-9
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Electric Vehicle (EV) Buyers in India: A Machine Learning Approach

Abstract: Electric mobility has been around for a long time. In recent years, with advancements in technology, electric vehicles (EVs) have shown a new potential to meet many of the challenges being faced by humanity. These challenges include increasing dependence on fossil fuels, environmental concerns, challenges posed by rapid urbanization, urban mobility, and employment. However, the adoption of electric vehicles has remained challenging despite consumers having a positive attitude toward EVs and big policy pushes b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Over the years EVs and their proliferation was impeded by apprehensions on higher initial costs, lifetime costs, charging concerns with lack of suitable points, and of course, a lack of overall awareness on the technology, as discovered by Tarei et al (2021); R. Kumar et al, 2020. It is logical that an understanding of barriers would assist in policy and decision making. Dixit & Singh (2022) used a machine learning model to predict EV purchase in India, arriving at the conclusion that while buyer-age, gender, salaries, environment issues, performance and lifetime cost, range-anxiety and market forces are significant predictors, some other expected parameters like education levels and government subsidies do not play a significant part. Patyal et al (2021) studied 13 barriers using ISM (Interpretive Structure Modelling) and MICMAC (Matriced' Impacts Croisés Appliquéeá un Classement), to help policymakers, and EV manufacturers to overcome design constraints.…”
Section: Barriers and Adoption Of Evsmentioning
confidence: 99%
“…Over the years EVs and their proliferation was impeded by apprehensions on higher initial costs, lifetime costs, charging concerns with lack of suitable points, and of course, a lack of overall awareness on the technology, as discovered by Tarei et al (2021); R. Kumar et al, 2020. It is logical that an understanding of barriers would assist in policy and decision making. Dixit & Singh (2022) used a machine learning model to predict EV purchase in India, arriving at the conclusion that while buyer-age, gender, salaries, environment issues, performance and lifetime cost, range-anxiety and market forces are significant predictors, some other expected parameters like education levels and government subsidies do not play a significant part. Patyal et al (2021) studied 13 barriers using ISM (Interpretive Structure Modelling) and MICMAC (Matriced' Impacts Croisés Appliquéeá un Classement), to help policymakers, and EV manufacturers to overcome design constraints.…”
Section: Barriers and Adoption Of Evsmentioning
confidence: 99%
“…Attributes of early adopters of EVs have been analyzed in several studies that have shown that regions with a higher GDP/capita and higher education levels have a more positive attitude towards EVs, due to their knowledge of the technology, and environmental awareness and responsibility [14,57]. We use the ratio of adults with a tertiary education and GDP/capita as a measure of the PU [58][59][60][61]. The TAM score is calculated based on the ranking of the following three factors between the regions: the charger density, based on Open Charge Map API [62], education levels, and GDP/capita, based on Eurostat data [63,64].…”
Section: Market Maturity Indexmentioning
confidence: 99%
“…In effect, EVs have become a promising alternative to IC Technology (JC Review, 2020). (Dixit & Singh, 2022).…”
Section: Consumer Preferencesmentioning
confidence: 99%